Filterless narrowband photodetectors enabled by controllable band modulation through ion migration: The case of halide perovskites - Yu Li; Shanshan Yu; Junjie Yang; Kai Zhang; Mingyu Hu; Weitao Qiu; Fumin Guo; Wei Qian; Sean Reinecke; Tao Chen; Makhsud I. Saidaminov; Jian Wang; et al. (InfoMat, 2024)
Abstract Narrowband photodetectors conventionally rely on optical structure design or bandpass filters to achieve the narrowband regime. Recently, a strategy for filterless narrowband photoresponse based on the charge collection narrowing (CCN) mechanism was reported. However, the CCN strategy requires an electrically and optically “thick” photoactive layer, which poses challenges in controlling the narrowband photoresponse. Here we propose a novel strategy for constructing narrowband photodetectors by leveraging the inherent ion migration in perovskites, which we term “band modulation narrowing” (BMN). By manipulating the ion migration with external stimuli such as illumination, temperature, and bias voltage, we can regulate in situ the energy‐band structure of perovskite photodetectors (PPDs) and hence their spectral response. Combining the Fermi energy levels obtained by the Kelvin probe force microscopy, the internal potential profiles from solar cell capacitance simulator simulation, and the anion accumulation revealed by the transient ion‐drift technique, we discover two critical mechanisms behind our BMN strategy: the extension of an optically active but electronically dead region proximal to the top electrode and the down‐bending energy bands near the electron transport layer. Our findings offer a case for harnessing the often‐annoying ion migration for developing advanced narrowband PPDs.